UPAYA PELAKSANAAN NILAI-NILAI AKHLAK KARIMAH DALAM PENDIDIKAN NILAI DI TINGKAT PERSEKOLAHAN - Usep Supriatna (FKIP Unirow Tuban, 2018)
The moral crisis that plagued some teenagers today, is one result of global developments and the progress of science and technology that is not matched by moral progress morals. The behavior of adolescents who tend to be irritable, lack of respect for the elderly, being rude, lacking discipline in worship, being a drug user, falling into free sex behavior and other deviant behavior has plagued most teenagers. Often also we hear, even long ago, the behavior of school-age children such as brawl between students, drinking, sexual harassment or rape, gank motor, primary or secondary school students commit suicide just for trivial reasons, low respect students to parents or teachers, memalak money his own friends and many more that all is a mirror of morals that have been not commendable to the students (students).